Pensiun Dini, Gaya Hidup, dan Pengeluaran Kesehatan Katastropik: Implikasi Ekonomi terhadap Penderita CVD di Indonesia - Hasya, Novira; Relaksana, Riki; Nur Huda Pranoto, Alexander; Y. M. Siregar, Adiatma (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study examines the effect of retirement on the risk of Cardiovascular Disease (CVD), a major Non-Communicable Disease (NCD) responsible for 73% of total deaths in Indonesia, with CVD accounting for 35%. Older adults, especially retirees, are more vulnerable to CVD due to declining physical function and reduced activity. Unhealthy lifestyles after retirement further elevate this risk. As a catastrophic and chronic illness, CVD also incurs high healthcare costs, absorbing around 30% of total hospital expenditures. Using IFLS data from 2007 and 2014, this study applies Pooled OLS, Pooled Logit, Fixed Effect (FE), and Fixed Effect Instrumental Variable (FE IV) methods. Findings show that retirement increases CVD risk by 0.170 percentage points (p < 0.01), while walking habit reduces by 0.006 percentage points (p < 0.05). Results from FE IV using State Pension Age (SPA) confirm this finding. The study suggests selectively increasing SPA and enhancing public support for walking activities.